AN EVALUATION OF INTERNAL EFFICIENCY OF JUNIOR SECONDARY EDUCATICN IN OYO STATE BETWEEN 1986 AND 1990 (1995)
The major problems facing educational system in Nigeria are those of resource allocation and resource utilisation. This study took stock of the resources in the Junior Secondary Schools in Oyo State and evaluated the degree of internal efficiency of Junior Secondary Education. The study focussed on: 1) making a critical analysis of the extent to which resources are made available to Junior Secondary Education in Oyo State; 2) identifying the extent to which the resources are being utilised; 3) finding the extent to which Junior Secondary education graduates are being admitted to technical and teacher training Colleges; 4) determining the extent of wastage rate reduction and improvement in students academic performance during the period; finding the extent to which the System is internally efficient; and 6) identifying causes of inefficiency, and suggesting recommendations for the elimination. To achieve these objectives, five research questions were raised and four hypotheses were tested. In providing answers for the research questions and testing the hypotheses, two sets of instruments: An Evaluation of Efficiency Questionnaire (EEQ I) for Principals and EEQ II for Guidance Counsellors were developed. Information was also collected from the Examinations Department, and also the Statistics Division of the Ministry of Education, Ibadan. For data analsysis, simple percentages were used to determine the growth trend, the reconstructed cohort method was employed to determine the wastage rates and wastage ratios, Chi-square, Spearman's Rank-Order Correlation Coefficients and t-test were used to determine the relationship between the internal and external efficiency of schools under study and to test the hypotheses. The findings show, among other things that: 1) the resources available for Junior Secondary Education in the area under study were not adequate. There were inadequate number of technical and science teachers. Physical and material resources were also inadequate; 2) some technical workshops, technical equipment and teachers were found not to be fully utilised; 3) there were inadequate technical and teacher training Colleges for those aspiring to proceed in technical and teacher training education. Up to 1990, both technical and teacher training Colleges were able to admit 6.3 per Cent of the total population of junior secondary education graduates of Oyo State and 21.7 per cent of the proportion that were not qualified for academic courses; 4) the teaching of most of the technical and vocational subjects had not started; 5) the internal efficiency , of Junior Secondary Education between 1986 and 1990 was: far from being perfect; 6) between 1986 and 1990, the internal efficiency of Junior Secondary Schools showed an improving trend; The wastage ratio decreased from 1.16 in 1988 to 1.07 in 1990 and the wastage rate decreased from 8.7 per Cent in 1988 to 4.7 per cent in 1990; 7) there was a significant relationship in the internal and external efficiency of the schools studied; 8) internal efficiency between schools in the areas of focus had no significant difference; 9) student-teacher ratio was found to be normal in the study area. The average was found to be 21:1.